All‐Carbon Nanoarchitectures as High‐Performance Separation Membranes with Superior Stability. (6th November 2015) - Goh, Kunli; Jiang, Wenchao; Karahan, Huseyin Enis; Zhai, Shengli; Wei, Li; Yu, Dingshan; Fane, Anthony G.; Wang, Rong; Chen, Yuan
Abstract : The application of graphene‐based membranes is hindered by their poor stability under practical hydrodynamic conditions. Here, nanocarbon architectures are designed by intercalating surface‐functionalized, small‐diameter, multi‐walled carbon nanotubes (MWCNTs) into reduced graphene oxide (rGO) sheets to create highly stable membranes with improved water permeability and enhanced membrane selectivity. With the intercalation of 10 nm diameter MWCNTs, the water permeability reaches 52.7 L m −2 h −1 bar −1, which is 4.8 times that of pristine rGO membrane and five to ten times higher than most commercial nanofiltration membranes. The membrane also attains almost 100% rejection for three organic dyes of different charges. More importantly, the membrane can endure a turbulent hydrodynamic flow with cross‐flow rates up to 2000 mL min −1 and a Reynolds number of 4667. Physicochemical characterization reveals that the inner graphitic walls of the MWCNTs can serve as spacers, while nanoscale rGO foliates on the outer walls interconnect with the assimilated rGO sheets to instill superior membrane stability. In contrast, intercalating with single‐walled nanotubes fails to reproduce such stability. Overall, this nanoarchitectured design is highly versatile in creating both graphene‐rich and CNT‐rich all‐carbon membranes with engineered nanochannels, and is regarded as a general approach in obtaining stable membranes for realizing practical applications of graphene‐based membranes. Abstract : All‐carbon nanoarchitectured membranes comprising reduced graphene oxide and multi‐walled carbon nanotubes exhibit a high water permeability, which is five to ten times higher than most commercial nanofiltration membranes. The membranes show almost 100% organic dye rejection and, most importantly, superior membrane stability under a turbulent hydrodynamic flow condition of 2000 mL min −1 and a Reynolds number of 4667.